2016
DOI: 10.3233/npm-16915113
|View full text |Cite
|
Sign up to set email alerts
|

Extensive use of vasodilator agents and functional echocardiography to monitor extremely-low-birth-weight infants in Japan

Abstract: National surveys were conducted in Japan to assess the current practices for circulatory management of extremely-low-birth-weight infants (ELBWIs) in acute phases. Approximately 80 and 100 institutions were surveyed in 2006 and 2011, respectively. Echocardiography was identified as an important diagnostic tool at 95% of the surveyed institutions. Furthermore, 74% of the institutions survey in 2011 used vasodilator agents. In 2011, the mean velocity of circumferential fiber shortening (mVcfc) and left ventricul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…More than 40 participants mentioned that Japan had faced a significantly low birth rate for more than two decades [ 59 ]. Without positive public health promotion, female health promotion, family caring, and sexual health promotion, the effective increase in quality cannot be supported [ 60 ]. The ideas about contribution to a country are uncommon for many public health studies, as most of the studies focused on the ideas about personal interests, career developments and education for the next generation [ 6 , 7 , 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…More than 40 participants mentioned that Japan had faced a significantly low birth rate for more than two decades [ 59 ]. Without positive public health promotion, female health promotion, family caring, and sexual health promotion, the effective increase in quality cannot be supported [ 60 ]. The ideas about contribution to a country are uncommon for many public health studies, as most of the studies focused on the ideas about personal interests, career developments and education for the next generation [ 6 , 7 , 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, circulatory management strategies that included echocardiographic assessment were found to be commonly used by Japanese neonatologists in a national survey about circulatory management for extremely low birthweight infants in 2011. That study showed that echocardiography was performed by neonatologist in all NICUs 26 . Thus, because echocardiographic assessment has been shown to be common in the NICUs, we assumed that evaluation for PH was performed in all units in this study when physicians in the institutions considered that a close examination of PH was necessary.…”
Section: Discussionmentioning
confidence: 99%
“…According to national surveys in Japan, the use of echocardiography and cardiovascular agents, including catecholamines and vasodilators, are part of the current practices for the circulatory management of ELBWIs. 38,39 This concept consists of tailored circulatory management based on the stress-velocity relationship in preterm infants. 40 That study showed that serious complications of intraventricular and/or pulmonary hemorrhages in ELBWIs were higher in infants with an excessive afterload, which resulted in a decrease in the function of the LV.…”
Section: Discussionmentioning
confidence: 99%